Peringkasan Multidokumen Otomatis dengan Menggunakan Log-Likelihood Ratio (LLR) dan Maximal Marginal Relevance (MMR) untuk Artikel dengan Topik Penyakit Menular Bahasa Indonesia - Ikhwan Nizwar Akhmad; Anto Satriyo Nugroho; Bambang Harjito (Indonesia Association of Computational Linguistics (INACL), 2018)
Increasing number of information available on the Internet, along with its benefit, also comes with various problems. Modern search engines are smart enough to bring the most relevant information, but the immense number of information provided often brings more confusion than clarity. This condition is known as information overload. Automatic multidocument summarization is a way to overcome this particular problem. Nevertheless, despite of being heavily studied more than 20 years, its implementations for Indonesian language are limited. In this paper, we reported our experimental results on multidocument summarization in Indonesian language. Articles about infectious disease is one of the ideal case study for multidocument summarization for Indonesian language. Information about infectious disease are essential for general public therefore many information about it is available on the Internet. This condition could trigger information overload when someone do an internet search in this topic. In this research, we try to implement multidocument summarization technique for articles with infectious disease topic in Bahasa Indonesia utilizing Log Likelihood Ratio (LLR) to obtain topic signatures and Maximal Marginal Relevance (MMR) to generate relevant summary with minimal information redundancy. Our summarization method generated a summary with 0.4 F-measure using ROUGE-S9 evalution. Also, we found that topic signature (with its accuracy) takes an important role on generating good summaries.